2010
DOI: 10.1021/jm1001748
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design and Synthesis of Potent, Ethylenediamine-Based, Mammalian Farnesyltransferase Inhibitors as Anticancer Agents

Abstract: A potent class of anticancer, human farnesyltransferase (hFTase) inhibitors has been identified by "piggy-backing" on potent, antimalarial inhibitors of Plasmodium falciparum farnesyltransferase (PfFTase). On the basis of a 4-fold substituted ethylenediamine scaffold, the inhibitors are structurally simple and readily derivatized, facilitating the extensive structure-activity relationship (SAR) study reported herein. Our most potent inhibitor is compound 1f, which exhibited an in vitro hFTase IC 50 value of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…It also showed notable whole‐cell inhibition activity (IC 50 = 90 nM) for H‐Ras processing. Further study indicated that the para ‐nitrile phenyl moiety could be stabilized by the Y361β residue via π–π stacking interaction, and was important structural fragment for the high activity . The results provide facile access to further design more potent and selective FTase inhibitors.…”
Section: Imidazoles As Anticancer Agentsmentioning
confidence: 88%
“…It also showed notable whole‐cell inhibition activity (IC 50 = 90 nM) for H‐Ras processing. Further study indicated that the para ‐nitrile phenyl moiety could be stabilized by the Y361β residue via π–π stacking interaction, and was important structural fragment for the high activity . The results provide facile access to further design more potent and selective FTase inhibitors.…”
Section: Imidazoles As Anticancer Agentsmentioning
confidence: 88%
“…In 2010, by using molecular modeling methods, Fletcher et al reported the discovery of two potent FTIs: inhibitors 1a and CVFM, and the structure of ethylenediamine was a novel scaffold [7]. A series of compounds were subsequently synthesized based on this novel scaffold, among which an inhibitor showed the highest inhibitory activity against FTase (IC 50 = 25 nM).…”
Section: Other Important Molecular Modeling Studiesmentioning
confidence: 99%
“…FTase and GGTase-I are prenyltransferases that target the carboxyl-terminal cysteine residues of the proteins with the CAAX motif (C refers to cysteine, A refers to any aliphatic amino acid and X refers to any amino acid) [6]. Owing to the essential roles of FTase and GGTase-I in the post-translational modifications of Ras proteins, a number of prenyltransferase inhibitors have been discovered and developed for the treatment of cancers [7,8], progeria [9], malaria [10], Trypanosoma cruzi [11], toxoplasmosis [12] and leishmaniasis [13]. In this review, the structures, biological functions and typical inhibitors of FTase and GGTase-I are summarized.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic search creates substantial attraction for the 5-membered ring compounds with three carbon and two adjacent nitrogen atoms. Pyrazole containing pharmacoactive agents play important role in medicinal chemistry and exhibit anti-inflammatory [2], antibacterial [3,4], anti-convulsant [5], anticancer [6,7], antiviral [8], antioxidant [9], anti-tubercular [10], and fungicidal [11] activity. Recently, a new pyrazolone compound, Edaravone (3-methyl-1-phenyl-2-pyrazolin-5-one, also known as MCI-186) a novel radical scavenger [12] has been developed as a drug for brain ischemia [13][14][15].…”
Section: Introductionmentioning
confidence: 99%